Lithium ion selective permeable membrane as well as preparation method and application thereof

By using the active layer of crosslinked polymer and metal organic frame in the lithium ion selection permeability membrane, the problem of poor lithium ion selection permeability and long-term use performance in the prior art is solved, and high selectivity and Stable ion flux.

CN119113829APending Publication Date: 2024-12-13GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411181320.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the application of existing zirconium-based metal organic framework (Zr-MOFs) materials in the field of ion separation, due to the compatibility between MOFs and organic matter, the selectivity and insufficient binding strength, resulting in lithium ions selective permeability and long-term use. Poor performance.

Method used

Using an active layer including crosslinked polymer and metal organic frame, a metal organic frame composite film is formed by polydopamine-modified base film and hydrothermal reaction, and crosslinking is combined with polyacrylic chloride monomer and polyamine monomer to form a cluster deletion. The defective lithium ion selects permeable membrane, reduces non-selective pores, and improves the lithium ion selective permeability and long-term use performance.

Benefits of technology

It is achieved to improve the selective permeability of lithium ions and long-term use performance while maintaining good ion flux, reduce non-selective pores, and enhance the adhesion strength and ion flux retention rate of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113829A_ABST
    Figure CN119113829A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion selective permeable membrane as well as a preparation method and application thereof, and belongs to the technical field of separation membranes. The lithium ion selective permeable membrane comprises a base membrane and an active layer on the surface of the base membrane, the active layer comprises a cross-linked polymer and a metal organic framework; the ratio of the sum of the specific pore volumes of the pores with the pore diameters lower than 2 nm to the sum of the specific pore volumes of the pores with the pore diameters lower than 100 nm in the lithium ion selective permeability membrane is 80% or above, the lithium ion selective permeability membrane has low non-selective pores, and the lithium ion selective permeability and long-term wearability are improved under the condition that good ion flux is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of separation membranes, and in particular to a lithium ion selective permeable membrane and a preparation method and application thereof. Background Art

[0002] Separation membranes based on metal organic frameworks (MOFs) are widely used in magnesium-lithium separation because of their precise pore size, high porosity, unique pore structure, and abundant molecular / ion-specific functional groups on the framework. Zirconium-based metal organic framework (Zr-MOFs) materials not only have the characteristics of large specific surface area, high porosity, and easy functionalization, but also have simple and rich synthesis methods and excellent stability. They show great application potential in adsorption, separation, catalysis, sensing and other fields. In the prior art, there are reports on the application of UiO-66 / 67 / 68 zirconium-based metal organic framework (Zr-MOFs) materials in the field of ion separation. These Zr-MOFs are composed of [Zr6O4(OH)4] 12+ The porous crystalline material formed by the self-assembly of hexanuclear metal clusters and aromatic polycarboxylic acid organic ligands belongs to the face-centered cubic system, has a coordination number of up to 12, and has a general molecular formula of Zr6O4(OH)4(L)6. The methods for loading MOFs on membrane materials generally include: ① blending to form a casting solution and then casting it into a membrane, ② MOFs polycrystalline membrane formed by nucleation and growth of MOFs on a substrate, ③ MOFs polyamide membrane prepared by embedding MOFs in a polyamide layer, and ④ channel membrane formed by filling the gaps of the substrate with MOFs; among them, the first to third methods, due to the poor compatibility of the two phases, lead to large non-selective pores between MOFs and organic matter (including polyamide and base membrane), resulting in low selectivity; and the low binding strength easily leads to the detachment of MOFs, resulting in performance degradation.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The object of the present invention is to provide a lithium ion selective permeable membrane and a preparation method and application thereof, aiming to reduce the non-selective pores of the membrane and improve the lithium ion selective permeability and long-term use performance while maintaining good ion flux.

[0005] The present invention can be implemented like this:

[0006] The first aspect of the present invention provides a lithium ion selective permeable membrane, comprising a base membrane and an active layer on the surface of the base membrane; the active layer comprises a cross-linked polymer and a metal organic framework; the ratio of the sum of the specific pore volumes of pores with a pore diameter less than 2 nm to the sum of the specific pore volumes of pores with a pore diameter less than 100 nm in the lithium ion selective permeable membrane is greater than 80%.

[0007] In some embodiments of the present invention, the lithium ion selective permeable membrane includes at least one of the following features:

[0008] Feature 1: The metal organic framework has cluster missing defects;

[0009] Feature 2: There is chemical crosslinking between the crosslinked polymer and the metal organic framework;

[0010] Feature 3: The base film is one of polysulfone, polyethersulfone, polyvinylidene fluoride, polypropylene, polyethylene, polyacrylonitrile, polyimide or polytetrafluoroethylene;

[0011] Feature 4: The thickness of the base film is 50 to 300 μm; preferably, the thickness of the base film is 90 to 150 μm;

[0012] Feature 5: The pore size of the basement membrane is 200 to 10000 nm; preferably, the pore size of the basement membrane is 500 to 1000 nm;

[0013] Feature 6: The sum of the specific pore volumes of the pores with a pore size of less than 100 nm in the lithium ion selective permeable membrane is 1.6 to 2.2 cm 3 / g;

[0014] Feature 7: The ratio of the sum of the specific pore volumes of pores with a pore diameter of less than 2 nm to the sum of the specific pore volumes of pores with a pore diameter of less than 100 nm in the lithium ion selective permeable membrane is 84% ​​to 92%.

[0015] In some embodiments of the present invention, the lithium ion selective permeable membrane further comprises at least one of the following features:

[0016] Feature 8: The X-ray diffraction test of the metal organic framework shows a diffuse reflection peak at 2θ=2-7°;

[0017] Feature 9: The metal organic framework is at least one of a UiO-66 derivative or a UiO-67 derivative;

[0018] Feature 10: The metal ion of the metal organic framework is a zirconium ion, the ligand includes a first ligand and a second ligand, the first ligand is 1,4-phthalic acid or 4,4'-biphenyldicarboxylic acid; the second ligand has the following formula I structure:

[0019]

[0020] In formula I, R1 to R5 are independently selected from one of the following groups: H, CH3 or NH2, and one or two of R1 to R5 are NH2; preferably, the second ligand is p-aminobenzoic acid or 3,5-diaminobenzoic acid;

[0021] Feature 11: The cross-linked polymer is formed by cross-linking polydopamine with polyacyl chloride monomers and polyamine monomers;

[0022] Feature 12: The sum of the specific pore volumes of the pores with a pore size of less than 100 nm in the lithium ion selective permeable membrane is 1.8 to 2 cm 3 / g.

[0023] In some embodiments of the present invention, the lithium ion selective permeable membrane further comprises at least one of the following features:

[0024] Feature 13: The lithium ion flux of the lithium ion selective permeable membrane after running for 1 hour is not less than 27×10 - 10 mol·s -1 cm -2 ;

[0025] Feature 14: The lithium ion selective permeability of the lithium ion selective permeability membrane is not less than 14.5;

[0026] Feature 15: The lithium ion flux retention rate of the lithium ion selective permeable membrane after continuous operation for 24 hours is not less than 97.3%.

[0027] A second aspect of the present invention provides a method for preparing a lithium ion selective permeable membrane, comprising the following steps:

[0028] Step 1: Covering the surface of the basement membrane with polydopamine to obtain a polydopamine-modified basement membrane;

[0029] Step 2: dissolving the zirconium salt, the first ligand, and the second ligand in a solvent to form a precursor solution, and immersing the polydopamine-modified base film in the precursor solution to perform a hydrothermal reaction to obtain a metal organic framework composite film;

[0030] Step 3: dissolving a polyacyl chloride monomer in a first solvent to form a polyacyl chloride monomer solution, dissolving a polyamine monomer in a second solvent to form a polyamine monomer solution, and applying the polyacyl chloride monomer solution and the polyamine monomer solution to the surface of the metal organic framework composite membrane in sequence to obtain a lithium ion selective permeable membrane.

[0031] In some embodiments of the present invention, the step 1 comprises the following steps: immersing the basement membrane in a buffer solution, adding dopamine hydrochloride to carry out a polymerization reaction, taking out and drying, thereby obtaining the polydopamine-modified basement membrane;

[0032] And / or, the buffer is a Tris-HCl buffer with a pH of 7.5 to 9.5;

[0033] And / or, the feeding ratio of the dopamine hydrochloride to the buffer solution is 1-3 g:1 L;

[0034] And / or, the polymerization reaction is carried out in a light-proof environment, the reaction temperature is 25° C. to 40° C., and the time is 12 to 24 hours;

[0035] And / or, the ratio of the area of ​​the basement membrane to the volume of the buffer solution is 1 cm 2 : 1~3mL.

[0036] In some embodiments of the present invention, the step 2 includes at least one of the following features:

[0037] Feature 1: The solvent is N,N-dimethylformamide or N,N-dimethylacetamide;

[0038] Feature 2: The molar ratio of the second ligand, the first ligand and the zirconium salt is 15-25:1:1;

[0039] Feature 3: The zirconium salt includes at least one of zirconium chloride and zirconium nitrate;

[0040] Feature 4: The molar concentration of zirconium ions in the precursor solution is 0.02 to 0.06 M;

[0041] Feature 5: The feed ratio of the polydopamine modified base film to the precursor solution is 1 cm 2 :1~3mL;

[0042] Feature 6: The temperature of the hydrothermal reaction is 100 to 140°C and the time is 12 to 36 hours.

[0043] In some embodiments of the present invention, the step three includes at least one of the following features:

[0044] Feature 7: The polyacyl chloride monomer includes at least one of phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride or trimesoyl chloride;

[0045] Feature 8: The polyamine monomer includes at least one of m-phenylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine or piperazine;

[0046] Feature 9: The first solvent includes one of n-hexane, n-octane, cyclohexane or n-heptane;

[0047] Feature 10: The second solvent is water;

[0048] Feature 11: The concentration of the polyacyl chloride monomer in the polyacyl chloride monomer solution is 0.1wt% to 0.5wt%;

[0049] Feature 12: The concentration of the polyamine monomer in the polyamine monomer solution is 0.5 wt% to 2 wt%.

[0050] The third aspect of the present invention is to provide the application of the above-mentioned lithium ion selective permeable membrane, wherein the lithium ion selective permeable membrane is used to extract lithium from lithium-containing liquid; preferably, the lithium ion selective permeable membrane is used to extract lithium by electrodialysis.

[0051] The beneficial effects of the present invention include:

[0052] The lithium ion selective permeable membrane provided by the present invention contains an active layer including a cross-linked polymer and a metal organic framework. The ratio of the sum of the specific pore volumes of pores with a pore diameter of less than 2 nm to the sum of the specific pore volumes of pores with a pore diameter of less than 100 nm is more than 80%. The membrane has relatively low non-selective pores, and improves lithium ion selective permeability and long-term use performance while maintaining good ion flux. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0054] Figure 1 Results of Experimental Example 1: SEM images of the surface (a) and cross section (b) of the lithium ion selective permeable membrane prepared in Example 1;

[0055] Figure 2 The results of Experimental Example 2: PXRD diffraction patterns of metal organic framework (Zr-MOFs) powders prepared at different second ligand concentrations;

[0056] Figure 3 The results of Experimental Example 3 are as follows: the pore size distribution curves of the lithium ion selective permeable membranes prepared in Example 1 and Comparative Examples 1 to 3;

[0057] Figure 4 This is the lithium extraction device of Experimental Example 4. DETAILED DESCRIPTION

[0058] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0059] The lithium ion selective permeable membrane provided by the present invention and its preparation method and application are described in detail below.

[0060] The present invention discloses a lithium ion selective permeable membrane, comprising a base membrane and an active layer on the surface of the base membrane; the active layer comprises a cross-linked polymer and a metal organic framework; the ratio of the sum of the specific pore volumes of pores with a pore diameter less than 2 nm to the sum of the specific pore volumes of pores with a pore diameter less than 100 nm in the lithium ion selective permeable membrane is greater than 80%.

[0061] The active layer of the above-mentioned lithium ion selective permeable membrane has fewer non-selective pores. The non-selective pores mentioned in the present invention refer to mesopores or macropores with a pore size greater than 2nm. Fewer non-selective pores under the same total pore volume are beneficial to maintaining flux while improving lithium ion selective permeability.

[0062] In a preferred embodiment of the present invention, the ratio of the sum of the specific pore volumes of pores with a pore diameter of less than 2 nm to the sum of the specific pore volumes of pores with a pore diameter of less than 100 nm in the lithium ion selective permeable membrane is 84% ​​to 92%.

[0063] In some embodiments of the present invention, the metal organic framework has a cluster missing defect; a cluster missing defect refers to the removal of a metal cluster and all ligands connected thereto, forming a coordination vacancy on an adjacent metal cluster; in some embodiments of the present invention, the metal cluster refers to [Zr6O4(OH)4] 12+ The ligands are phthalic acid compounds (first ligand) and aminobenzoic acid compounds (second ligand). Since the second ligand competes with the first ligand for coordination, defects are generated. The defects will not lead to a significant decrease in the structure and performance of Zr-MOFs materials, which is mainly attributed to [Zr6O4(OH)4] 12+ The high degree of coordination enables zirconium-based metal-organic frameworks (Zr-MOFs) to maintain a stable framework structure in the absence of a large number of organic ligands or metal clusters, and the appropriate degree of defects can change its physical and chemical properties without destroying the metal-organic framework structure, significantly improving the ion flux.

[0064] The metal organic framework with cluster missing defects has a diffuse reflection peak at 2θ=2-7° in its X-ray diffraction test due to changes in the crystal structure.

[0065] In some embodiments of the present invention, the metal organic framework is at least one of a UiO-66 derivative or a UiO-67 derivative, wherein UiO-66 and UiO-67 are both zirconium-based metal organic frameworks, and the ligands are 1,4-phthalic acid and 4,4'-biphenyldicarboxylic acid, respectively; the derivative of UiO-66 or UiO-67 refers to the addition of a second ligand to regulate its defects.

[0066] In some embodiments of the present invention, the ligand of the metal organic framework includes a first ligand and a second ligand, the first ligand is 1,4-benzenedicarboxylic acid or 4,4'-biphenyledicarboxylic acid; the second ligand has the following structure I:

[0067]

[0068] In Formula I, R1 to R5 are independently selected from one of the following groups: H, CH3 or NH2, and one or two of R1 to R5 are NH2.

[0069] In some embodiments of the present invention, the second ligand is p-aminobenzoic acid or 3,5-diaminobenzoic acid.

[0070] The addition of the second ligand in the present invention can cause cluster missing defects in the metal organic framework, and at the same time introduce amine groups on the surface of the metal organic framework. The amine groups can be cross-linked with the cross-linked polymer through chemical bonds, so that the polymer phase and the metal organic framework crystal particles are tightly combined, thereby reducing non-selective pores and improving the adhesion strength of the metal organic framework in the active layer, thereby improving the lithium ion selective permeability and improving the long-term performance of the membrane.

[0071] In some embodiments of the present invention, the base film is one of polysulfone, polyethersulfone, polyvinylidene fluoride, polypropylene, polyethylene, polyacrylonitrile, polyimide or polytetrafluoroethylene.

[0072] In an optional embodiment, the base film has a thickness of 50 to 300 μm, preferably 90 to 150 μm.

[0073] In an optional embodiment, the pore size of the base membrane is 200 to 10000 nm, preferably 500 to 1000 nm.

[0074] In some embodiments of the present invention, the sum of the specific pore volumes of the pores with a pore size of less than 100 nm in the lithium ion selective permeable membrane is 1.6 to 2.2 cm 3 / g, preferably 1.8 to 2 cm 3 / g.

[0075] The total pore volume affects the ion flux of the membrane. If the pore volume is too low, the ion flux is too low, and if the pore volume is too high, the ion flux is too high, both of which will lead to low lithium permeability.

[0076] In some embodiments of the present invention, the cross-linked polymer is formed by cross-linking polydopamine with polyacyl chloride monomers and polyamine monomers.

[0077] In an optional embodiment, the polyacyl chloride monomer includes at least one of phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride or trimesoyl chloride.

[0078] In an optional embodiment, the polyamine monomer includes at least one of m-phenylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine or piperazine.

[0079] Polydopamine, the metal organic framework surface and the polyamine monomer all contain amine groups, which can undergo acylation reaction with the polyacyl chloride monomer to form a cross-linked network, so that the active layer is tightly combined as a whole, thereby reducing non-selective pores.

[0080] In some embodiments of the present invention, the lithium ion flux of the lithium ion selective permeable membrane after running for 1 hour is not less than 27×10 -10 mol·s -1 cm -2 .

[0081] In some embodiments of the present invention, the lithium ion selective permability of the lithium ion selective membrane is not less than 14.5.

[0082] In some embodiments of the present invention, the lithium ion flux retention rate of the lithium ion selective permeable membrane after continuous operation for 24 hours is not less than 97.3%.

[0083] The method for preparing the lithium ion selective permeable membrane provided by the present invention comprises the following steps:

[0084] Step 1: Covering the surface of the basement membrane with polydopamine to obtain a polydopamine-modified basement membrane;

[0085] Step 2: dissolving the zirconium salt, the first ligand, and the second ligand in a solvent to form a precursor solution, and immersing the polydopamine-modified base film in the precursor solution to perform a hydrothermal reaction to obtain a metal organic framework composite film;

[0086] Step 3: dissolving a polyacyl chloride monomer in a first solvent to form a polyacyl chloride monomer solution, dissolving a polyamine monomer in a second solvent to form a polyamine monomer solution, and applying the polyacyl chloride monomer solution and the polyamine monomer solution to the surface of the metal organic framework composite membrane in sequence to obtain a lithium ion selective permeable membrane.

[0087] The present invention first prepares a polydopamine modified base membrane so that the surface of the base membrane contains a large number of catechol groups, which have good complexing ability for zirconium ions and can serve as an "anchor" to allow the metal organic framework Zr-MOFs to grow in situ on the surface of the base membrane; in addition, the amine groups contained in the polydopamine can serve as cross-linking active sites to cross-link with the metal organic framework, polyamine monomers and polyacyl chloride monomers, so that the compatibility of each component is greatly increased, tightly combined, and the dispersibility and bonding strength of the metal organic framework are improved, thereby improving the lithium ion selective permeability and long-term use performance of the membrane.

[0088] In some embodiments of the present invention, step one is specifically as follows: immersing the basement membrane in a buffer solution, adding dopamine hydrochloride to carry out a polymerization reaction, taking it out and drying it to obtain a polydopamine-modified basement membrane.

[0089] In an optional embodiment, the buffer is a Tris-HCl buffer with a pH of 7.5 to 9.5.

[0090] In an optional embodiment, the feed ratio of the dopamine hydrochloride to the buffer solution is 1-3 g:1L.

[0091] In an optional embodiment, the polymerization reaction is carried out in a light-proof environment, the reaction temperature is 25° C. to 40° C., and the time is 12 to 24 hours.

[0092] In an optional embodiment, the ratio of the area of ​​the basement membrane to the volume of the buffer is 1 cm 2 : 1~3mL.

[0093] In an optional embodiment, the solvent in step 2 is N,N-dimethylformamide (DMF) or N,N-dimethylacetamide (DMAc).

[0094] In an optional embodiment, in step 2, the molar ratio of the second ligand, the first ligand, and the zirconium salt is 15-25:1:1.

[0095] In an optional embodiment, the zirconium salt in step 2 includes at least one of zirconium chloride and zirconium nitrate.

[0096] In an optional embodiment, the molar concentration of zirconium ions in the precursor solution in step 2 is 0.02-0.06M.

[0097] In an optional embodiment, the feed ratio of the polydopamine modified base film to the precursor solution in step 2 is 1 cm 2 : 1-3 mL, that is, the ratio of the area of ​​the polydopamine-modified basement membrane to the volume of the precursor solution is 1 cm 2 : 1~3mL.

[0098] In an optional embodiment, the temperature of the hydrothermal reaction in step 2 is 100-140° C., and the time is 12-36 hours.

[0099] In an optional embodiment, the polyacyl chloride monomer in step three includes at least one of phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride or trimesoyl chloride.

[0100] In an optional embodiment, the polyamine monomer in step three includes at least one of m-phenylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine or piperazine.

[0101] In an optional embodiment, in step three, the first solvent includes one of n-hexane, n-octane, cyclohexane or n-heptane.

[0102] In an optional embodiment, in step three, the second solvent is water.

[0103] In an optional embodiment, the concentration of the polyacyl chloride monomer in the polyacyl chloride monomer solution in step three is 0.1 wt % to 0.5 wt %.

[0104] In an optional embodiment, the concentration of the polyamine monomer in the polyamine monomer solution in step three is 0.5 wt % to 2 wt %.

[0105] The present invention also provides the application of the lithium ion selective permeable membrane, which is used to extract lithium from lithium-containing liquid, including but not limited to adsorption, membrane separation, electrodialysis, etc. In some embodiments of the present invention, an electrodialysis device equipped with the lithium ion selective permeable membrane is used to extract lithium.

[0106] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0107] Example 1

[0108] This embodiment provides a lithium ion selective permeable membrane, and the preparation method is as follows:

[0109] (1) Preparation of polydopamine modified basement membrane

[0110] The polyethersulfone base membrane (thickness of 150 μm, pore size of 400-1200 nm) was immersed in a Tris-HCl buffer solution of pH=8.5, dopamine hydrochloride was added, and the polymerization reaction was stirred at 30°C for 24 hours in the dark, and then taken out and vacuum dried at 100°C to obtain a polydopamine modified base membrane. The concentration of dopamine hydrochloride in the buffer solution was 2 g / L (i.e., the feed ratio of dopamine hydrochloride to the buffer solution was 2 g:1 L); the area of ​​the base membrane and the volume ratio of the buffer solution were 1 cm 2 :2mL.

[0111] (2) Preparation of metal organic framework composite membranes

[0112] Weigh p-aminobenzoic acid, terephthalic acid and zirconium chloride and dissolve them in DMF to obtain a precursor solution. Place the precursor solution in an autoclave, then place the polydopamine-modified base membrane at the bottom of the reactor and react at 120°C for 24 hours. Take out the membrane, rinse it with DMF and water three times respectively, and vacuum dry it at 80°C to obtain a metal-organic framework composite membrane with lattice defects.

[0113] The ratio of the area of ​​the polydopamine modified base film to the volume of the precursor solution is 1 cm 2:2mL.

[0114] The molar ratio of p-aminobenzoic acid, terephthalic acid and zirconium chloride is 20:1:1, and the concentration of zirconium chloride in the precursor solution is 0.04M.

[0115] (3) Lithium ion selective permeable membrane

[0116] The method comprises dissolving trimesoyl chloride in n-hexane to form a 0.25 wt % trimesoyl chloride solution; dissolving a polyamine in water to form a polyamine solution with a concentration of 1.4 wt %; soaking the metal organic framework composite membrane in the trimesoyl chloride solution and letting it stand for 10 minutes, then taking it out and soaking it in a polyamine solution and heating it to 75° C. for a cross-linking reaction for 15 minutes, taking it out and rinsing it with ethanol and water for 3 times respectively and drying it to obtain a lithium ion selective permeable membrane.

[0117] The polyamine is a mixture of m-phenylenediamine and piperazine in a molar ratio of 2:1.

[0118] Example 2

[0119] The difference from Example 1 is that in step (2), 3,5-diaminobenzoic acid is used instead of p-aminobenzoic acid.

[0120] Example 3

[0121] The difference from Example 1 is that in step (2), 4-amino-3-methylbenzoic acid is used instead of p-aminobenzoic acid, and diphenyl dicarboxylic acid is used instead of terephthalic acid.

[0122] Example 4

[0123] The difference from Example 1 is that in step (2), the molar ratio of p-aminobenzoic acid, terephthalic acid and zirconium chloride is 15:1:1.

[0124] Example 5

[0125] The difference from Example 1 is that the molar ratio of p-aminobenzoic acid, terephthalic acid and zirconium chloride in step (2) is 25:1:1.

[0126] Example 6

[0127] This embodiment provides a lithium ion selective permeable membrane, and the preparation method is as follows:

[0128] (1) Preparation of polydopamine modified basement membrane

[0129] The polypropylene base film (thickness of 120 μm, pore size of 200-800 nm) was immersed in a Tris-HCl buffer solution of pH=7.5, dopamine hydrochloride was added, and the polymerization reaction was stirred at 25°C for 24 hours in the dark, and then taken out and vacuum dried at 100°C to obtain a polydopamine modified base film. The concentration of dopamine hydrochloride in the buffer solution was 1 g / L (i.e., the feed ratio of dopamine hydrochloride to the buffer solution was 1 g:1 L); the area of ​​the base film and the volume ratio of the buffer solution were 1 cm 2 :1mL.

[0130] (2) Preparation of metal organic framework composite membranes

[0131] Weigh p-aminobenzoic acid, terephthalic acid and zirconium nitrate and dissolve them in DMF to obtain a precursor solution. Place the precursor solution in an autoclave, then place the polydopamine-modified base membrane at the bottom of the reactor, and react at 100°C for 24 hours. Take out the membrane, rinse it with DMF and water three times respectively, and vacuum dry it at 80°C to obtain a metal-organic framework composite membrane with lattice defects.

[0132] The ratio of the area of ​​the polydopamine modified base film to the volume of the precursor solution is 1 cm 2 :3mL.

[0133] The molar ratio of p-aminobenzoic acid, terephthalic acid and zirconium nitrate is 20:1:1, and the concentration of zirconium nitrate in the precursor solution is 0.02M.

[0134] (3) Lithium ion selective permeable membrane

[0135] Dissolve terephthaloyl chloride in cyclohexane to form a 0.5wt% terephthaloyl chloride solution; dissolve piperazine in water to form a 0.5wt% piperazine solution; soak the metal organic framework composite membrane in the terephthaloyl chloride solution and let it stand for 5 minutes, then take it out and soak it in the piperazine solution and heat it to 65°C for cross-linking reaction for 20 minutes, take it out and rinse it with ethanol and water three times respectively and dry it to obtain a lithium ion selective permeable membrane.

[0136] Example 7

[0137] This embodiment provides a lithium ion selective permeable membrane, and the preparation method is as follows:

[0138] (1) Preparation of polydopamine modified basement membrane

[0139] The polyacrylonitrile base membrane (thickness of 200 μm, pore size of 200-1000 nm) was immersed in a Tris-HCl buffer solution of pH=9.5, dopamine hydrochloride was added, and the polymerization reaction was stirred at 40°C for 12 hours in the dark, and then taken out and vacuum dried at 100°C to obtain a polydopamine modified base membrane. The concentration of dopamine hydrochloride in the buffer solution was 3 g / L (i.e., the feed ratio of dopamine hydrochloride to the buffer solution was 3 g:1 L); the area of ​​the base membrane and the volume ratio of the buffer solution were 1 cm 2 :3mL.

[0140] (2) Preparation of metal organic framework composite membranes

[0141] Weigh p-aminobenzoic acid, terephthalic acid and zirconium nitrate and dissolve them in DMF to obtain a precursor solution. Place the precursor solution in an autoclave, then place the polydopamine-modified base membrane at the bottom of the reactor and react at 140°C for 24 hours. Take out the membrane, rinse it with DMF and water three times respectively, and vacuum dry it at 80°C to obtain a metal-organic framework composite membrane with lattice defects.

[0142] The ratio of the area of ​​the polydopamine modified base film to the volume of the precursor solution is 1 cm 2 :1mL.

[0143] The molar ratio of p-aminobenzoic acid, terephthalic acid and zirconium nitrate is 20:1:1, and the concentration of zirconium nitrate in the precursor solution is 0.06M.

[0144] (3) Lithium ion selective permeable membrane

[0145] Dissolve isophthaloyl chloride in n-octane to form a 0.1wt% isophthaloyl chloride solution; dissolve hexamethylenediamine in water to form a 2wt% hexamethylenediamine solution; soak the metal organic framework composite membrane in the isophthaloyl chloride solution and let it stand for 10 minutes, then take it out and soak it in the hexamethylenediamine solution and heat it to 85°C for a cross-linking reaction for 10 minutes, take it out and rinse it with ethanol and water three times respectively and then dry it to obtain a lithium ion selective permeable membrane.

[0146] Comparative Example 1

[0147] The difference from Example 1 is that the base membrane is not coated with polydopamine, that is, step (1) is omitted, and the polyethersulfone base membrane replaces the polydopamine-modified base membrane in step (2).

[0148] Comparative Example 2

[0149] The difference from Example 1 is that p-aminobenzoic acid is not added in step (2).

[0150] Comparative Example 3

[0151] This comparative example provides a metal organic framework-based membrane, and the preparation method is as follows:

[0152] (1) Preparation of Metal-Organic Frameworks

[0153] Weigh p-aminobenzoic acid, terephthalic acid, and zirconium chloride and dissolve them in DMF to obtain a precursor solution, place the precursor solution in an autoclave, react at 120°C for 24 hours, collect the white product by centrifugation after cooling, rinse with DMF and water, and dry at 80°C to obtain a metal organic framework. The molar ratio of p-aminobenzoic acid, terephthalic acid, and zirconium chloride is 20:1:1, and the concentration of zirconium chloride in the precursor solution is 0.04M.

[0154] (2) Preparation of metal organic framework-based membranes

[0155] The metal organic framework is dispersed in a polyamine aqueous solution with a concentration of 1.4wt%, and ultrasonicated for 30 minutes to obtain a suspension. The polyethersulfone-based membrane is immersed in the above solution, taken out after standing for 10 minutes, and the excess aqueous solution is gently wiped with a paper towel, and then immersed in a 0.25wt% trimesoyl chloride solution again, heated to 75°C, and reacted for 15 minutes to obtain a composite membrane. The polyamine is a mixture of m-phenylenediamine and piperazine in a molar ratio of 2:1, the solvent of the trimesoyl chloride solution is n-hexane, and the ratio of the metal organic framework to the polyamine aqueous solution is 1g:200mL.

[0156] Comparative Example 4

[0157] The difference from Example 1 is that in step (2), 2-aminoterephthalic acid is used instead of p-aminobenzoic acid.

[0158] Test Example 1

[0159] The surface (a) and cross section (b) of the lithium ion selective permeable membrane prepared in Example 1 were observed by scanning electron microscopy. The obtained SEM images are as follows: Figure 1 shown.

[0160] from Figure 1 As can be seen in (a), the surface of the base film contains granular metal organic framework crystals, which are evenly distributed and tightly bound in the active layer; Figure 1 As can be seen in (b), the active layer is thin and evenly distributed on the surface of the base film.

[0161] Test Example 2

[0162] Metal organic framework (Zr-MOFs) powders at different defect modifier concentrations were prepared by hydrothermal method and subjected to PXRD test, as follows: ① p-Aminobenzoic acid, terephthalic acid and zirconium chloride were weighed and dissolved in DMF, the obtained precursor solution was placed in an autoclave, reacted at 120°C for 24h, cooled and centrifuged to collect the white product, washed with DMF and water, and dried at 80°C to obtain Zr-MOFs powder material; wherein Zr in the precursor solution 4+ The concentration is 0.04M, the molar ratio of terephthalic acid and zirconium chloride is 1:1, and the molar amount of p-aminobenzoic acid is 0, 7, 15, 25, and 30 of the molar amount of terephthalic acid, respectively. Figure 2 0eq, 7eq, 15eq, 25eq, 30eq in the sample; ② The Bruker D8 diffractometer was used for testing, using Cu-Kα radiation (λ=1.5418A), with a scanning range of 2-50°, and the sample preparation method was as follows: 30 mg of the Zr-MOFs powder material sample prepared above was dispersed on a glass PXRD sample holder with a diameter of 2.5 cm, and then a piece of stretched plastic film was used to flatten and keep the sample in an appropriate position for measurement. The results are shown in the attached Figure 2 .

[0163] As can be seen from the figure, after the defect modifier is added, a weaker and wider diffuse reflection peak is observed in the range of 2θ=2-7°, indicating that there are cluster missing defects in the material, and as more p-aminobenzoic acid is added, the intensity of the diffuse reflection peak increases, indicating that the degree of defect increases accordingly.

[0164] Test Example 3

[0165] The pore structure analysis was performed on the sample membranes prepared in the embodiments and comparative examples and their raw material base membranes. The N2 isothermal adsorption-desorption curves of the sample membranes to be tested were obtained using ASAP2020M specific surface area and micropore adsorption analyzer. The pore size distribution diagram was then calculated according to the BJH model, and the pore volume information was obtained by integrating the pore size distribution diagram.

[0166] It should be noted that the pore size range of the N2 isothermal adsorption-desorption curve is 0-200 nm. First, the pore size distribution analysis of the three base membranes used in the embodiments of the present invention is performed, and the results of the sample membranes are subtracted as the background to obtain the porous structure information of the active layer. The sum of the specific pore volumes of pores below 100 nm and the ratio of the sum of the specific pore volumes of pores below 2 nm to the sum of the specific pore volumes of pores below 100 nm of the sample membranes prepared in the embodiments and comparative examples are listed in Table 1. The pore size distribution diagrams of Embodiment 1 and Comparative Examples 1 to 3 are shown in the attached Figure 3 .

[0167] Since the membrane prepared in the embodiment of the present invention has no pore distribution between 100 and 200 nm, Figure 3Only the pore size distribution of 0 to 100 nm is shown. Figure 3 It can be seen that the four sample membranes have almost no pore size distribution after 10nm. Compared with Comparative Examples 1 to 3, the pore size of Example 1 is mainly distributed in the micropore range, and the sum of the specific pore volumes of pores below 100nm is also smaller than that of Comparative Examples 1 to 3. The ratio of the sum of the specific pore volumes of pores with a pore size below 2nm to the sum of the specific pore volumes of pores with a pore size below 100nm in the sample membranes prepared in Comparative Examples 1 and 3 is low, and the sum of the specific pore volumes of pores with a pore size below 100nm is high. The reason is that Comparative Example 1 does not modify the base membrane with polydopamine, and the metal organic framework of Comparative Example 3 is not in situ grown on the base membrane, so that the compatibility of the components is poor and the degree of binding is low; Comparative Example 2 is compared with Example 1. Comparative Example 2 does not add the second ligand, that is, the surface of the metal organic framework of Comparative Example 2 does not contain active amine groups that are chemically cross-linked with the cross-linked polymer, so its degree of binding with the cross-linked polymer is low, so the pore size distribution appears after 2nm.

[0168] Test Example 4

[0169] The lithium extraction performance of the sample membranes prepared in the examples and comparative examples was tested. The separation membranes were assembled into an electrodialysis lithium extraction device, and the ion flux (J) and lithium ion permselectivity (P) were tested.

[0170] Electrodialysis lithium extraction device as attached Figure 4 As shown, it consists of a polarization chamber (cathode polarization chamber and anode polarization chamber), a concentration chamber and a desalination chamber, wherein the electrodes are titanium electrodes with a ruthenium oxide coating. The polarization chamber is filled with a 0.3M sodium sulfate solution, and the desalination chamber is filled with a Li+ solution with a metal ion concentration of 0.1M. + and Mg 2+ The concentration chamber was filled with a 0.01 M KCl solution. The electrodialysis membrane group consisted of CEM (AMX, purchased from Asahi Kasei Corporation, Japan), the sample membrane to be tested, and CEM. The volume of the solution in each compartment was 100 mL, the pump flow rate was 20 mL / min, and the constant current mode was used to determine the Li in the concentration chamber by ICP-OES. + Mg 2+ The concentration of lithium ions was calculated according to the following formula:

[0171]

[0172] Where J is the ion flux (mol·h -1 ·m -2 ), C0 and C t are the ion concentrations at time 0 and time t in the concentration chamber (mol / L), V is the liquid volume of the concentration chamber in the device (L), and A is the effective area of ​​the sample membrane to be tested (m2 ).

[0173]

[0174] Where P is the lithium ion permeability, J Li and J Mg are the ion fluxes of lithium ions and magnesium ions at time t, respectively, Mg and C Li are the concentrations of lithium ions and magnesium ions in the desalination chamber at time t, respectively.

[0175] Lithium ion flux (J) of the sample membranes prepared in the examples and comparative examples after the first operation for 1 h Li ) and lithium ion permselectivity (P) as well as J after 24 h of continuous operation compared with that after 1 h of initial operation Li The lithium ion flux retention rates are shown in Table 1.

[0176] Table 1

[0177]

[0178]

[0179] As can be seen from Table 1, the embodiment has higher comprehensive performance than the comparative example. Specifically, in comparative example 1, the base membrane is not modified with polydopamine, so the metal organic framework loading amount of the obtained membrane is small, and the cross-linking structure changes, resulting in an increase in non-selective pores, which in turn leads to an increase in lithium ion flux and a decrease in lithium selective permeability; in comparative example 2, no second ligand is added, so the metal organic framework surface is not chemically cross-linked with the cross-linking polymer, and the bonding tightness between the components decreases, resulting in an increase in non-selective pores, which in turn leads to an increase in lithium ion flux and a decrease in lithium selective permeability; in comparative example 3, a metal organic framework is first prepared and then compounded with a base membrane. Compared with the embodiment, the metal organic framework is in situ grown on the base membrane, and the dispersion of the metal organic framework powder is poor, resulting in a decrease in the bonding tightness of the components, resulting in an increase in non-selective pores, which in turn leads to an increase in lithium ion flux and a decrease in lithium selective permeability; in comparative example 4, relative to Example 1, 2-aminoterephthalic acid is used as the second ligand. Compared with the second ligand defined in the present invention, the prepared metal organic framework has a lower degree of defects, resulting in a decrease in lithium ion flux and poor long-term performance.

[0180] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium ion selective permeable membrane, characterized in that: The lithium ion selective permeable membrane comprises a base membrane and an active layer on the surface of the base membrane; the active layer comprises a cross-linked polymer and a metal organic framework; the ratio of the sum of the specific pore volumes of pores with a pore diameter less than 2 nm to the sum of the specific pore volumes of pores with a pore diameter less than 100 nm in the lithium ion selective permeable membrane is greater than 80%.

2. The lithium ion selective permeable membrane according to claim 1, characterized in that: The lithium ion selective permeable membrane includes at least one of the following features: Feature 1: The metal organic framework has cluster missing defects; Feature 2: There is chemical crosslinking between the crosslinked polymer and the metal organic framework; Feature 3: The base film is one of polysulfone, polyethersulfone, polyvinylidene fluoride, polypropylene, polyethylene, polyacrylonitrile, polyimide or polytetrafluoroethylene; Feature 4: The thickness of the base film is 50 to 300 μm; Feature 5: The pore size of the basement membrane is 200 to 10000 nm; Feature 6: The sum of the specific pore volumes of the pores with a pore size of less than 100 nm in the lithium ion selective permeable membrane is 1.6 to 2.2 cm 3 / g; Feature 7: The ratio of the sum of the specific pore volumes of pores with a pore diameter of less than 2 nm to the sum of the specific pore volumes of pores with a pore diameter of less than 100 nm in the lithium ion selective permeable membrane is 84% ​​to 92%.

3. The lithium ion selective permeable membrane according to claim 1 or 2, characterized in that: The lithium ion selective permeable membrane further comprises at least one of the following features: Feature 8: The X-ray diffraction test of the metal organic framework shows a diffuse reflection peak at 2θ=2-7°; Feature 9: The metal organic framework is at least one of a UiO-66 derivative or a UiO-67 derivative; Feature 10: The metal ion of the metal organic framework is a zirconium ion, the ligand includes a first ligand and a second ligand, the first ligand is 1,4-phthalic acid or 4,4'-biphenyldicarboxylic acid; the second ligand has the following formula I structure: In formula I, R1 to R5 are independently selected from one of the following groups: H, CH3 or NH2, and one or two of R1 to R5 are NH2; preferably, the second ligand is p-aminobenzoic acid or 3,5-diaminobenzoic acid; Feature 11: The cross-linked polymer is formed by cross-linking polydopamine with polyacyl chloride monomers and polyamine monomers; feature 12. The sum of the specific pore volumes of the pores with a pore size of less than 100 nm in the lithium ion selective permeable membrane is 1.8 to 2 cm 3 / g.

4. The lithium ion selective permeable membrane according to any one of claims 1 to 3, characterized in that: The lithium ion selective permeable membrane further comprises at least one of the following features: Feature 13: The lithium ion flux of the lithium ion selective permeable membrane after running for 1 hour is not less than 27×10 -10 mol·s -1 cm -2 ; Feature 14: The lithium ion selective permeability of the lithium ion selective permeability membrane is not less than 14.5; Feature 15: The lithium ion flux retention rate of the lithium ion selective membrane after continuous operation for 24 hours is not less than 97.3%.

5. A method for preparing a lithium ion selective permeable membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Covering the surface of the basement membrane with polydopamine to obtain a polydopamine-modified basement membrane; Step 2: dissolving the zirconium salt, the first ligand, and the second ligand in a solvent to form a precursor solution, and immersing the polydopamine-modified base film in the precursor solution to perform a hydrothermal reaction to obtain a metal organic framework composite film; Step 3: dissolving a polyacyl chloride monomer in a first solvent to form a polyacyl chloride monomer solution, dissolving a polyamine monomer in a second solvent to form a polyamine monomer solution, and applying the polyacyl chloride monomer solution and the polyamine monomer solution to the surface of the metal organic framework composite membrane in sequence to obtain a lithium ion selective permeable membrane.

6. The preparation method according to claim 5, characterized in that: The step 1 comprises the following steps: immersing the basement membrane in a buffer solution, adding dopamine hydrochloride to carry out a polymerization reaction, taking out and drying, thereby obtaining the polydopamine-modified basement membrane; And / or, the buffer is a Tris-HCl buffer with a pH of 7.5 to 9.5; And / or, the feeding ratio of the dopamine hydrochloride to the buffer solution is 1-3 g:1 L; And / or, the polymerization reaction is carried out in a light-proof environment, the reaction temperature is 25° C. to 40° C., and the time is 12 to 24 hours; And / or, the ratio of the area of ​​the basement membrane to the volume of the buffer solution is 1 cm 2 : 1~3mL.

7. The preparation method according to claim 5, characterized in that: The step 2 includes at least one of the following features: Feature 1: The solvent is N,N-dimethylformamide or N,N-dimethylacetamide; Feature 2: The molar ratio of the second ligand, the first ligand and the zirconium salt is 15-25:1:1; Feature 3: The zirconium salt includes at least one of zirconium chloride and zirconium nitrate; Feature 4: The molar concentration of zirconium ions in the precursor solution is 0.02 to 0.06 M; Feature 5: The feed ratio of the polydopamine modified base film to the precursor solution is 1 cm 2 :1~3mL; Feature 6: The temperature of the hydrothermal reaction is 100 to 140°C and the time is 12 to 36 hours.

8. The preparation method according to claim 5, characterized in that: The step three includes at least one of the following features: Feature 7: The polyacyl chloride monomer includes at least one of phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride or trimesoyl chloride; Feature 8: The polyamine monomer includes at least one of m-phenylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine or piperazine; Feature 9: The first solvent includes one of n-hexane, n-octane, cyclohexane or n-heptane; feature 10: The second solvent is water; Feature 11: The concentration of the polyacyl chloride monomer in the polyacyl chloride monomer solution is 0.1wt% to 0.5wt%; Feature 12: The concentration of the polyamine monomer in the polyamine monomer solution is 0.5 wt% to 2 wt%.

9. Use of the lithium ion selective permeable membrane according to any one of claims 1 to 4, characterized in that: The lithium ion selective permeable membrane is used for extracting lithium from lithium-containing liquid.

10. The use according to claim 9, characterized in that: The lithium ion selective permeable membrane is used for extracting lithium by electrodialysis.

Citation Information

Cited By

  • Metal ion induced nanocluster membrane material and preparation method thereof

    CN119588184A